Effect of sodium alginate on the physicochemical and sensory properties of vegan surimi - Afifah Mohd Sobri; Lay-Jing Seow; Utthapon Issara; Nur Ain Ab Rahman; Nurul Huda; Eng Keng Seow (jurnal1, 2023)
Sodium alginate at different concentrations (0% - Control, 0.25% - F1, 0.50% - F2, and 0.75% - F3) were added to the vegan surimi, and the effect to the physicochemical and sensory properties of vegan surimi was assessed. The addition of 0.75% sodium alginate has significantly (p<0.05) improved the folding test score of F3 from 3.00 to 3.67. A significant (p<0.05) increase was observed in hardness, gumminess, and chewiness of F3 with the recorded value at 3.01, 2.56, and 2.43 kg, respectively. Besides, moisture content (70.82%), water holding capacity (78.36%), and lightness (quality indicator) of F3 were significantly (p<0.05) enhanced with the addition of sodium alginate. In sensory evaluation, the most preferred product was F1 (0.25% sodium alginate) in terms of texture (7.00), taste (7.17), and overall acceptability (7.17) based on the 9-point Hedonic testing. In conclusion, the results suggest the potential of sodium alginate in the improvement of physicochemical and sensory properties of vegan surimi.